The making of a transnational capitalist class : corporate power in the twenty-first century - Carroll, William K. (Zed, 2010)
With an indepth analysis that spans three decades, The Making of a Transnational Capitalist Class maps the changing field of power generated by elite relations among the world's largest corporations and related political organizations. Using social network analysis, William Carroll charts the making of a capitalist class which reaches beyond national forms of organization into a global field, but which faces spirited opposition from below in an ongoing struggle over alternative global futures.